Evaluating green supply chain performance based on ESG and financial indicators - Zeng, Huiling; Li, Rita Yi Man; Zeng, Liyun (Frontiers in Environmental Science, 2022)
To reduce carbon emission and enhance social development simultaneously, “Environmental, Social and Governance” (ESG) plays a significant role in supply chain management. The study collected 2,400 financial data and ESG performance about 200 companies from the Clean 200 list of global public companies from 2019 to 2021. It aimed to: (1) evaluate green supply chain performance based on financial indicators and corporate’s ESG performance; (2) use the entropy weight method (EWM) to determine the weight of ESG elements; (3) evaluate this ESG-based evaluation model. The results showed that operational performance had the highest weight, followed by environmental performance, and profitability ranked the last. The results suggested that managers should focus more on the governance and environment rather than emphasizing short-term financial benefits. It contributes to the literature by incorporating ESG to evaluate green supply chain performance, which is the first of its kind. The results would be beneficial when people wish to select supply chain partners and listed companies. They are also conducive to companies’ managers when they submit financial reports that need to report ESG performance.